Performance characteristics of a liquid e-fuel cell. (1st September 2021) - Shi, Xingyi; Huo, Xiaoyu; Esan, Oladapo Christopher; An, Liang; Zhao, T.S.
Graphical abstract: Highlights: Performance characteristics of a liquid e-fuel cell are studied. Effects of operating and structural design parameters are examined. A power density of 857.0 mW cm −2 and an energy efficiency of 41.8% are achieved. Abstract: Liquid fuel cell has been regarded as a promising power generation system due to its high energy density, instant recharging, and ease of fuel handling. However, its widespread commercialization is still being hampered by its limited performance resulting from the poor reaction kinetics of the conventional alcohol fuels. Recently, a liquid e-fuel cell, utilizing an electrically rechargeable liquid fuel (e-fuel), has been proposed and demonstrated with significant performance advancement in comparison to conventional liquid fuel cells. In this work, we study its performance characteristics and examine the effects of the operating and structural design parameters. Experimentally, it is found that this e-fuel cell, operating at 60 °C impressively results in an open-circuit voltage of 1.15 V, a maximum current density of 1980 mA cm −2, a peak power density of 857.0 mW cm −2, and an energy efficiency of 41.8%. These significant results thus present that the liquid e-fuel cell opens a window of opportunity for breakthroughs in advancement of fuel cell technology.